Intensified dewetting of polystyrene thin film under water-solvent mixture: role of solvent composition - Yadav P.; Verma A. (My University, 2025)
Intensified dewetting of ultrathin polystyrene (PS) films induced by immersing in a homogeneous mixture of good solvent and water was previously reported to push the limits of dewetting to the sub-100 nm scale. Here, we systematically analyse the role of dewetting mixture composition, i.e. solvent to water ratio, on the length scales of instability. The effect of the solvent concentration in the dewetting mixture on the instability wavelength (λ) and droplet diameter (d) are determined. The instability wavelength (λ) for 50 nm thick PS film was found to be decreasing from nearly 17 to 7 μ m as the solvent concentration is decreased from 95 to 35% in the dewetting mixture. This is significantly smaller than the instability wavelength in air, which is nearly 50μm for the same PS film. The solubility of PS in the dewetting mixture is also examined and the mechanism of observed variation in the length scale is proposed. © 2020, Indian Academy of Sciences.